If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 45 = 79 + -1h Solving 45 = 79 + -1h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add 'h' to each side of the equation. 45 + h = 79 + -1h + h Combine like terms: -1h + h = 0 45 + h = 79 + 0 45 + h = 79 Add '-45' to each side of the equation. 45 + -45 + h = 79 + -45 Combine like terms: 45 + -45 = 0 0 + h = 79 + -45 h = 79 + -45 Combine like terms: 79 + -45 = 34 h = 34 Simplifying h = 34
| 7c+3=17 | | 45=54-d | | 47=54-d | | (8Z^2)+14z+5=0 | | 62=81-r | | 12i+7r-14i= | | 12i+7r-14y= | | 3t+1=7t | | 6a^2-13a+15=6a | | 95-b=73 | | 0=2x^2-20+50 | | f-25=25 | | 19t+5-17t=23 | | 1/10s= | | v-39=22 | | 28=35-a | | 4x^2=484 | | 3*1/5 | | 7x-y+8x+5y= | | 480ms= | | 6x+10=5x+16 | | 62=92-s | | 9+24=-4 | | 26=u-17 | | 45-3x=9-9x | | 46-j=31 | | 4x^2-20x+26=1 | | 84=x+0.2x | | 60=69-f | | 18x+14x-27y= | | 3=89-g | | 52-q=32 |